2007
DOI: 10.1111/j.1532-849x.2007.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Prosthodontists in Private Practice: Current and Future Conditions of Practice in the United States (Part I)

Abstract: The United States spends about $1.8 billion on prosthodontic services provided by prosthodontists in private practice. Prosthodontists spend $1.1 billion dollars in expenses and treat an estimated 1.1 million patients per year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…At the specialty level, prosthodontics embraces its interactive and leadership role as part of a therapy team, while in the comprehensive primary care responsibility, a prosthodontist often acts as a single provider. A recent publication showed that implant therapy, both placement and restoration, accounted for 37% of the revenue for the average prosthodontic practice 22 . Dental implants placed by prosthodontists accounted for 12% of the revenue 23 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the specialty level, prosthodontics embraces its interactive and leadership role as part of a therapy team, while in the comprehensive primary care responsibility, a prosthodontist often acts as a single provider. A recent publication showed that implant therapy, both placement and restoration, accounted for 37% of the revenue for the average prosthodontic practice 22 . Dental implants placed by prosthodontists accounted for 12% of the revenue 23 .…”
mentioning
confidence: 99%
“…A recent publication showed that implant therapy, both placement and restoration, accounted for 37% of the revenue for the average prosthodontic practice. 22 Dental implants placed by prosthodontists accounted for 12% of the revenue. 23 A survey by the Advanced Education in Prosthodontics (AEP) program directors in the United States and Canada reported that implant surgical training has become an essential part of prosthodontic program curricula.…”
mentioning
confidence: 99%
“…In a previous article the ADA estimated there were about 335,900 completed implant services rendered by prosthodontists 2 . In 2007, the ADA reported that based on their findings from the 2005 to 2006 Survey of Dental Services Rendered, 10 there were 620,820 implant services (D6000‐D6199) completed by prosthodontists.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of practicing prosthodontists was estimated to be 3404 in 2006, and 2707 (79.5%) were estimated to be in private practice. In an article prepared in 2007, it was stated that the private practice of prosthodontics was an attractive profession based on the current net income of prosthodontists in comparison to other occupations 2 . Part of these conclusions were based on results from the 2005 Survey of Prosthodontists conducted by the American College of Prosthodontists (ACP) 3…”
mentioning
confidence: 99%
“…In recent conversations with several Graduate Prosthodontics Program directors, the applicant pool for the class entering in 2009 looks outstanding! And, given the great publicity we've received over the past few years from Forbes Magazine , initially ranking Prosthodontists sixth in highest‐paying jobs (the third highest in dentistry behind Orthodontists and Oral and Maxillofacial Surgeons), and ranking us first in “Well‐paying Rare Jobs,” along with the information provided by Kent Nash and David Pfeifer (immediate Past‐president of the College) on the return on investment for careers in Prosthodontics, 1–4 the predoctoral students have begun to figure it out. And, if you haven't actually read the Nash and Pfeifer articles, download them, read them, and pass them along to a first or second year dental student!…”
Section: Program Type: # Accredited Programs: Average Tuition/feesmentioning
confidence: 99%